Arytenoid Repositioning Device. (March 2014) - Hoffman, Henry T.; Heaford, Andrew C.; Dailey, Seth H.; Bock, Jonathan M.; Van Daele, Douglas J.; Ahlrichs-Hanson, Jan S.; Quebbemann, Greg J.; Johnson, Micaela N.; Boltz, Justin E.; Tiedt, Sean L.
Objectives: We report development of a device and technique to manage laryngeal paralysis through minimal-access arytenoid adduction (for unilateral paralysis) and arytenoid abduction (for bilateral paralysis). Methods: A human cadaver study coupled with directed engineering was used to develop instrumentation designed to secure the muscular process of the arytenoid into favorable adducted or abducted positions. Digital video, photography, and 3-dimensional computed tomographic (CT) imaging of cadaveric larynges were done to evaluate the surgical technique. Results: Testing of prototypes identified the ideal implant to be a 0.36-mm wire with a distal spring-wound coil placed through a trocar via a small drill hole in the anterior thyroid cartilage. An endoscopic view of transilluminated light through the pyriform sinus mucosa identified the tip location of the trocar adjacent to the muscular process of the arytenoid cartilage. Placement of the device through the trocar permitted rotation to engage the muscular process and/or adjacent soft tissue with the distal coil. Implant fixation to the thyroid cartilage positioned the vocal cord into either adduction or abduction. Three-dimensional CT imaging coupled with review of the video documentation established the feasibility of this technique. Conclusions: We confirm the feasibility of minimal-access arytenoid adduction and abduction through development of a new technique and device.